The Relationship Between Measures of Impulsivity and Clinical Characteristics of Patients With Alcohol Use Disorder - Klimanova, S; Trusova, A; Berezina, A; Gvozdetsky, A (KnE Life Sciences, 2018)
The current article presents findings on the interaction between impulsivity features and clinical characteristics of patients with alcohol use disorders (AUD). Patients (n = 88), who were completing detoxification program for the symptoms of AUD, were recruited for the study. They completed biographical questionnaire, Penn Craving Scale (PACS), self-report screening measure of the symptoms of adult ADHD (ASRS v.1.1) and underwent a series of experimental tasks (Delay Discounting Task (DDT), Stroop Task, Continuous Performance Test-Identical Pairs (CPT-IP), Tower of London (ToL)). Two distinct groups of impulsivity features were identified using cluster analysis. One group, which was comprised of DDT and ToL measures, described the level of impulsivity during the decision-making process. The second group included Stroop task and CPT-IP measures and expressed the level of response inhibition and interference control. In addition, the model of interaction between measures of impulsivity and clinical characteristics of patients was developed. The self-report measure of inattention and hyperactivity had significant effect on the level of craving and the duration of remission. No significant relationships were observed between DDT clinical characteristics. Keywords: impulsivity, alcohol use disorder, delay discounting, stroop task, Tower of London, CPT-IP, craving, ASRS